The impact of corporate governance and corporate social responsibility on firms’ performance. Evidence from the US market. - SARIDIS, VASILEIOS (2018)
The target of this study is to interpret the relation between factors that are not financial such as corporate governance, social responsibility and firms’ financial performance. The content of this research is of major interest as the role of sustainable finance has been vastly analyzed throughout the new millennium while firms’ performance is considered to be one of the most examined topics in the field of corporate finance. Recent literarure has focused on the significance of the sustainable finance based on the argument that, after the 2008 financial crisis, there is a major trend related to investors concerned about sustainable growth. Namely, a very large number of investors seeks to combine financial performance with positive social impact, by funding firms that actively contribute to sustainable development. This paper uses regression analysis (with year and industry effects) to find if there is any connection between the variables. Two data samples (All-industries data sample and Manufacturing industry data sample) have been used for the period of 2010-2016. Regarding all-industries data sample, the results show that there is a positive correlation between board size, social supply chain management, R&D expenditures and firms’ performance. On the other hand, executives compensation linked to better corporate governance/social responsibility is negatively correlated. I did not find any statistically significant connection between the percentage of independent directors, the percentage of women on board, CEO duality and financial performance. Moreover, as far as the secondary analysis (based on Manufacturing firms) is concerned, the results show that there is a positive relationship between CEO duality and firms’ profitability. Independent directors, R&D expenditures and social supply chain management are negatively connected. Here, no relationship found between the percentage of women on board, executives compensation linked to better corporate governance/social responsibility and financial performance. Finally, this dissertation underlines the importance of taking into consideration the effects of corporate governance and social responsibility where investors, stakeholders and corporations are considering sustainable growth and future development.